Vegetation based climate solutions for soil management in smallholder farmlands of Kabale and Rubanda districts, Uganda - Ndemere, Julius; Brahima, Kone; Bamwerinde, Wilson (Springer Nature Singapore, 2025)
Understanding and appreciating climate solutions for soil management in smallholder farmlands are paramount. These climate solutions inform smallholder farmers’ actions, choices, decisions and priorities to tackle specific climate change problems and opportunities. The study used structured and semi structured questionnaires to collect field data to ascertain smallholder farmers’ knowledge about vegetation based climate solutions for soil management in Kabale and Rubanda districts, Uganda. A purposive sampling technique was used to collect data from 367 smallholder farmer household head respondents. Regression model, specifically linear to test multicollinearity and multinomial logistic and descriptive statistics was utilised to examine vegetation based climate solutions for soil management. Vegetation based climate solutions such as crop residues, selected trees, Napier grass and Seteria grass (dependent) and gender, age and marital status, and level of education information (independent) were determined predictor variables. The findings revealed that both genders, males (51.5%) and females (48.5%), witnessed climate change as demonstrated in Fig. 2 . The chi-square test (χ 2  = 376.337) indicated a significant difference between smallholder farmers’ implementing climate solutions. The study observed positive Kendall’s tau (0.357 and 0.118) and a p -value (0.002 and 0.289) of temperature and rainfall respectively. Most farmers (69.2%) relied on fellow farmers as a major source of climate information to manage soil and enhance soil fertility. Vegetation based climate solutions 33.8%, (planting Napier grass, selected tree species, and crop residues) were revealed as suitable and effective soil management interventions to control soil erosion and fertility improvement in smallholder farmlands. Climate solutions were significantly influenced by level of education (0.000) and farmland size (0.001) at 0.05. Therefore, there is a need to incorporate vegetation based climate solutions into government development programmes and agendas to enhance soil fertility and erosion management in smallholder farmers’ farmlands with a focus on livelihood improvement through increasing crop yields and hunger alleviation.